Electric field estimation of deep transcranial magnetic stimulation clinically used for the treatment of neuropsychiatric disorders in anatomical head models. (May 2017) - Parazzini, Marta; Fiocchi, Serena; Chiaramello, Emma; Roth, Yiftach; Zangen, Abraham; Ravazzani, Paolo
Highlights: We evaluated the electric field spatial distribution of H1 coil and figure-of-eight coil in different brain regions We used computation method applied to two realistic human models We used coil positioning traditionally used in clinical experiments We showed the importance of knowing the electric field spatial distribution to interpret the outcomes of the experimental results and to optimize the treatments Abstract: Literature studies showed the ability to treat neuropsychiatric disorders using H1 coil, developed for the deep Transcranial Magnetic Stimulation (dTMS). Despite the positive results of the clinical studies, the electric field (E ) distributions inside the brain induced by this coil when it is positioned on the scalp according to the clinical studies themselves are not yet precisely estimated. This study aims to characterize theE distributions due to the H1 coil in the brain of two realistic human models by computational electromagnetic techniques and to compare them with the ones due to the figure-of-8 coil, traditionally used in TMS and positioned as such to simulate the clinical experiments. Despite inter-individual differences, our results show that the dorsolateral prefrontal cortex is the region preferentially stimulated by both H1 and figure-of-8 coil when they are placed in the position on the scalp according to the clinical studies, with a more broad and non-focal distribution in the case of H1 coil. Moreover, the H1 coil spreads more than the figure-of-8 coil both in the prefrontal cortex and medial prefrontal cortex and towards some deeper brain structures and it is characterized by a higher penetration depth in the frontal lobe. This work highlights the importance of the knowledge of the electric field distribution in the brain tissues to interpret the outcomes of the experimental studies and to optimize the treatments.